Pensamiento, Pandemia y Big Data : El Impacto Sociocultural Del Coronavirus en el Espacio Iberoamericano. - Gallego Cuiñas, Ana.; Pérez Tapias, José Antonio (Berlin/Boston : Walter de Gruyter GmbH, 2022)
The series presents interdisciplinary studies harnessing humanistic as well as digital tools to offer innovative approaches to literary studies, linguistics, critical theory and philosophy in the 21st-century Ibero-American space. Along three main lines of research - digital corpora, experimental linguistics, and the relation between literature, critique and big data - it transcends dataism to open new perspectives within Digital Humanities.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books